Determinants of job satisfaction: A systematic review - Katherine Micaela Caceres Fuentes,; Luis Miguel Romero Echevarria,; Carlos Mallqui Vitor,; Thony Marco Gomez Maraza,; Carlos Alberto Murillo Salazar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Promoting job satisfaction is essential in today's market due to a greater appreciation of human talent and the growing interest in attracting and retaining it. For this study, a literature review was carried out following the PRISMA methodology with the intention of identifying the determining factors of job satisfaction. To do this, a total of 31 publications obtained from Scopus (19) and SciELO (12) were compiled, of which 21 were selected for analysis. Research positions job satisfaction not as an objective in itself, but as a predictor of productivity and commitment to the organization. In addition, the importance of meeting workers' expectations from an emotional level was highlighted, through their empowerment and promotion of well-being.